A colaboração crítica na formação de professor para atuar na EAD - Garcia, Luiz Miguel Martins (2015)
This study aimed at critically understanding the construction of a teacher training practice between the researcher-teacher and a teacher of a BA distance course in Management. It is based on the following questions: What are the knowledge production modes in the teacher's practice with learners in the forums? How do the teacher-student relations observed in the forums permeate the reflective sessions between teacher and researcher? What are the distance relations established among participants? Which results are revealed? How do the distance relations between the direct participants (teacher and researcher) and the indirect participants (teacher and students) affect the concept and define distance knowledge production? What defines distance education? The theoretical and methodological bases of the work arise from the Dialectical and Historical Materialism (MARX, 1845-46/2007) which considers research as a movement from the practice, real world, to the theory, ideal world. It also considered that the relations between the subjects occur in dialectical movements motivated by a need and mediated by instruments; Socio-Historical Theory (VYGOTSKY, 1935/1998), which inserts language as a genuine instrument in human relations and discusses learning and development from the perspective of the ZPD; Activity Theory (LEONTIEV, 1972); Language in critical-collaborative relations (MAGALHÃES, 2012); Argumentation (LIBERALI e FUGA, 2012; MAGALHÃES, NININ e LESSA, 2014); Critical teacher education (LIBERALI, 2006); Interactive approaches to Distance Education (VALENTE, 2003a); Transactional distance (MOORE, 1993/2002). The results demonstrated the impossibility of knowledge production in teacher and students relationship in the QeA forums, as the preference was given to the use of the Message tool, which provides private relations (student-teacher) instead of collective forums (teacher-student and student-student). Therefore, these non-existent relations in the forums influenced and transformed the perspective of the relations between teacher and researcher in reflective sessions, becoming a locus of critical teacher education in Distance Education contexts. As far as the relations of distance between the participants are concerned, they showed that the knowledge production occurs in a transmissive approach, from the perspective of virtualization of the traditional school and with the teacher centralizing the actions and distributing "knowledge". This research showed that the concept of distance needs to be thoroughly rethought in the current scenario as the technological resources which have characterized Distance Education so far deconstructing its spatiotemporal foundations more and more. Besides, it allowed the construction of a critical-collaborative practice between researcher and teacher enabling questioning, negotiating and reframing the sense of Distance Education. At the end of the meetings, the teacher considers that the priority is not to discuss the new digital technologies as well as their possibilities, but to deepen the pedagogical discussion in critical perspective in order to know how to use the available tools in each context better